Antecedents and consequences of online customer brand engagement in business-to-business in an emerging market - Sibanda, Tonderai Gilbert (University of the Witwatersrand, Johannesburg, 2023)
The purpose of the research is to study the antecedents and consequences of online CBE in the context of emerging markets and B2B. The role of mediators between CBE and its consequences is yet to be fully explored. CBE has not been studied much in the B2B context in emerging markets. Data was collected from ICT decision makers in South African and Kenya through an online survey on Qualtrics. In total, four studies were done, namely, a pilot study in South Africa, two main studies in South Africa using different samples and the last one in Kenya. A PLS structural equation modelling (SEM) was performed to test the hypothesis using SmartPLS4. A mediation analysis was done to check the effect on mediators between online CBE and its consequences. The research shows that involvement, brand equity, participation and brand love are antecedents of online CBE. Relationship quality amplifies the effect of online CBE on its consequences, namely loyalty, brand advocacy, brand preference and purchase intention. This research provides business and brand managers with ideas on how to approach online CBE in B2B. It shows that a multidimensional approach to online CBE is better because each of the online CBE components are affected by the antecedents differently and each one has a different effect on the consequences. Mediators amplify the effect of online CBE on its consequences. This thesis makes a contribution in four ways: a) It makes an incremental scholarly contribution by bringing together constructs from various cognate theories and study areas relating to relationship management; and investigates how the predictors of customer brand engagement and how customer brand engagement predicts the outcome variables, b) It makes a practical contribution in the sense that it adds to our understanding of the factors that influence customer brand engagement and the expected outcomes of customer brand engagement in practice, c) It also makes a contribution relating to the study of emerging market contexts by drawing data from more than one emerging market country, namely, South Africa and Kenya d) The thesis delves into highly significant and relevant topics, with a notable focus on introducing the construct (CBE) in the B2B context, ii incorporating data from emerging markets. This pioneering inclusion of CBE in a new context highlights the thesis's exceptional contribution, as well as originality, bridging a research gap and expanding knowledge in the field.
A thesis submitted to Wits Business School, Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfillment of the Degree of Doctor of Philosophy, Johannesburg 2023
Keywords: Online customer brand engagement (CBE); Relationship quality; Emerging markets; Quantitative; Business-to-business (B2B); UCTD; SDG-8: Decent work and economic growth